Revolutionizing COVID-19 Treatment: Saving High-Risk Cardiac Patients from Severity, Hospitalization, and Death with Plant-Based Diets and Dietary Supplements - Mulijono, Dasaad; Hutapea, Albert M; Lister, I Nyoman E; Sudaryo, Mondastri K; Umniyati, Helwiah (Archives of Clinical and Biomedical Research, 2024)
Introduction: In the Asian region, Indonesia has the second-highest COVID-19 death toll and the highest mortality rate, which provides the background for this study. The research is centered on the elderly cardiology population with multiple comorbidities, who have demonstrated a propensity for extended recovery periods, heightened severity, hospitalization, and mortality upon contracting the COVID-19 infection. Objective: This research distinguishes itself by employing a distinct strategy, assessing the efficacy of plant-based diets (PBDs) and supplement interventions in reducing the severity, hospitalization, recovery, and mortality rates of high-risk COVID-19 elderly cardiology patients. This innovative approach could potentially yield valuable information on the management of COVID-19 and facilitate better preparation for future pandemics. Methods: A longitudinal investigation was undertaken at an institutional level between April 2020 and June 2023. The study comprised 1,750 elderly cardiology patients who were put on PBDs and had their metabolic parameters managed before contracting COVID-19 infection. Throughout the course of COVID-19 treatment, these patients received rigorous PBDs and supplementations that aimed to enhance the PBDs' anti-viral, antiinflammatory, antioxidant, antithrombotic, and immunomodulatory effects against the SARS-CoV-2 virus. The quality, amount, and processing of the PBDs were strictly monitored, and supplementation was incorporated to optimize the PBDs' effectiveness against the virus. Results: The findings were noteworthy. Our patients exhibited quicker recuperation times (12±1.4 days as opposed to 21±7 days), fewer instances of severe illness (2% compared to 10-20%), and a lower incidence of hospitalizations (0% versus 5-10%) and fatalities (0% as opposed to 15- 17%) when contrasted with the general elderly COVID-19 population in Indonesia (GECPI). Conclusion: PBDs and supplement interventions have been demonstrated to effectively reduce COVID-19 recovery time, severity, hospitalization, and mortality among elderly cardiology patients with multiple comorbidities. Effective management of patient's metabolic and chronic inflammatory diseases before contracting COVID-19 is crucial to achieving optimal patient outcomes. It should be implemented for all patients to prepare them for future respiratory viral pandemics.